2005
DOI: 10.1093/bioinformatics/bti426
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and simulation of cancer immunoprevention vaccine

Abstract: http://www.dmi.unict.it/CIG/suppdata_bioinf.html.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 16 publications
3
69
0
Order By: Relevance
“…SIMTRIPLEX has been used to model immunoprevention vaccines Pappalardo et al 2005Pappalardo et al , 2006Lollini et al 2006) and atherosclerosis (Pappalardo et al 2008a). Rather than describe the work covered in the preceding papers, here we will consider the modelling and computational challenges that we have faced.…”
Section: Modelling the Immune Systemmentioning
confidence: 99%
“…SIMTRIPLEX has been used to model immunoprevention vaccines Pappalardo et al 2005Pappalardo et al , 2006Lollini et al 2006) and atherosclerosis (Pappalardo et al 2008a). Rather than describe the work covered in the preceding papers, here we will consider the modelling and computational challenges that we have faced.…”
Section: Modelling the Immune Systemmentioning
confidence: 99%
“…However, this differential efficacy of the cancer vaccine in prophylaxis and therapy has been proven by several other studies evaluating the feasibility of a cancer vaccine with tolerized tumor antigens. [42][43][44][45][46] Novakovic et al 44 found that the proportion of protected mice was 75-100% by vaccination of irradiated melanoma tumor cells with CpG ODN in a prophylactic setting whereas the rates of cured mice were only 11.1-21.1% in a therapeutic setting. Garcia-Hernandez Mde et al 45 recently reported that prophylactic vaccination with a prostate antigen, six-transmembrane epithelial antigen of prostate, significantly delayed tumor growth and improved survival whereas therapeutic vaccination induced a modest delay in the growth of established prostate tumors.…”
Section: Differential Antitumor Effects Of Il-23 H-t Jin Et Almentioning
confidence: 99%
“…Moreover, in a HER-2/neu transgenic mouse model which closely mimics the natural history of human tumors, early vaccination produced a significantly delay in the onset of tumors, whereas late vaccination was completely devoid of an effect in comparison to untreated control mice. 42,46 There are many reasons why vaccination is poorly effective as a tumor therapy. 1 One of them is the lag time of inducing tumor-specific adaptive immunity, leading to the generation of an immunosuppressive environment by the growing tumor in a therapeutic setting.…”
Section: Differential Antitumor Effects Of Il-23 H-t Jin Et Almentioning
confidence: 99%
“…In so doing, they assembled a number of up-to-date immunological theories in one single coherent and generalpurpose model that has shown to be a valid starting point to explore different medical/clinical subjects. In the past years we have developed specialized versions of the Celada-Seiden model to study HIV-1 infection, EBV infection, hypersensitivity reactions and cancer immunoprevention (described respectively in [12][13][14][15] Figure 1. The aim of the presented simulation platform is to provide enough complexity to be able to implement virtually any process in immunology.…”
Section: Introductionmentioning
confidence: 99%